Analysis of the Contribution of ASEAN Countries in Supporting Sustainable Tourism in Indonesia - Arnanda Ajisaputra; Nurtjahja Juniarsa (PT. EQUATOR SINAR AKADEMIA, 2023)
This research aims to find out the contribution of ASEAN countries in supporting sustainable tourism in Indonesia as seen from the number of tourist visits from 2014-2021. Using the VECM method, the results showed that: (1) ASEAN countries with dominating tourist visits to Indonesia are: Malaysia, Singapore, Philippines, and Thailand; (2) there are long and short-term effects on tourist arrivals of the four ASEAN countries to Indonesia; (3) if there is a shock to the number of tourist arrivals from one of the ASEAN countries to Indonesia, it will resonate the number of tourist arrivals from the other three ASEAN countries; (4) if one of the ASEAN countries experiences a shock to the number of their tourist arrivals to Indonesia, it will first have an impact on the next period in that country, after which it will shake the other three ASEAN countries in the adjacent period. It is recommended that government and private organizations engaged in tourism, as well as the public, support the tourism liberalization program while still paying attention to local wisdom and various forms of assistance so that the number of tourist visits to Indonesia, especially in four ASEAN countries, remains stable, to enable the tourism sector to provide maximum tourism foreign exchange earnings.